(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Ring yarns are increasingly used in Denim fabrics. Fibre arrangement in spun yarn influences the various yarn properties. Spinning triangle in case of compact spinning remains smaller than that of conventional ring spinning process; hence the migration of fibres takes place to different extents in yarns spun using these technologies. As a result with the advent of compact spinning technology overall quality of yarn has improved significantly. In view to study the effect of compacting the fibre batt on fibre migration, denim yarns of count 8Ne and 12Ne have been produced using compaction attachments of pneumatic principle based on Marzoli's Olefil and mechanical magnetic principle based on Rotorcraft's RoCos, on the same spindles of Marzoli ringframe. Fibre migration in terms of mean fibre position, RMS deviation and migration intensity has been determined using tracer fibre technique under CCD camera attached with a computer having image processing software. Experimental results have been analyzed using two way ANOVA with replication technique. It was observed that, migration intensity of normal ring yarns is significantly higher than compact yarns whereas migration intensity of mechanical magnetic compact yarns is significantly higher than that of pneumatic compact yarns. There are no significant changes noted in mean fibre position and RMS deviation. These yarn samples are also evaluated for their various yarn characteristics viz. tensile strength, elongation, unevenness, hairiness, etc to determine the structure- property interrelationship.